Flag of the Hamlet of Aklavik - Farnel, Sharon (2017)
This flag of the Hamlet of Aklavik was displayed in a public building. It is yellow with black bars on either side of a circle which surrounds a triangular shield on which there is a door mouse below an open book. The words "Never Say Die" appear in an arc below the shield. The words Hamlet of Aklavik appear in in arc above the shield.